Non-Adherence to Treatment and Health Consequences among Iraqi Patients with Hypertension - Dr. Raid Abd Almuhssin Hamood; Dr. Mayyadah Adil Raheem (Academic Journal of Clinicians, 2024)
Hypertension is a chronic cardiovascular disease that most often affects adults worldwide and is a leading cause of premature mortality. Adherence to treatment, along with quality of life, are fundamental principles for patients’ adaptation to lifestyle changes. life by improving your health. The study was conducted to determine the quality of life and adherence to therapeutic therapy in patients diagnosed with high blood pressure in the districts of Isidro Ayora Alto and Bajo in the province of Loja between April and August 2022, using a quantitative approach. The cross-sectional group included 60 people who met the inclusion and exclusion criteria, to which the Minihal and Morisky-Green test was applied, and 88.33% (n = 53) were found to have poor adherence to hypertension treatment, 11, 67% (n = 7 ) have a high quality of life; 55% (n=33) average quality of life and 33.22% (n=20) low quality of life. It is concluded that in this population there is a significant association (p<0.01) between adherence to hypertension treatment and quality of life, and this is a positive association: the higher the adherence, the higher the quality of life. Key words: cardiovascular diseases, health-related quality of life, somatic manifestations, emotional state, physical well-being, primary health care.